PELATIHAN ECOBRICK UNTUK MENGURANGI SAMPAH PLASTIK GUNA MEWUJUDKAN CIBIYUK CANTIK MELALUI KREATIVITAS ECOBRICK - Nur Fani Arisnawati; Yunita Lisnaningtyas Utami (Jurnal Padamu Negeri, 2025)
Plastic waste has become an urgent environmental problem worldwide. Plastic offers many benefits, its environmental impact and long-lasting nature require responsible use, recycling and disposal practices to reduce negative impacts on the environment. Environmental cleanliness is a shared responsibility for both children and adults. In the midst of these challenges, creative initiatives such as Ecobricks have emerged as solutions that have the potential to reduce the negative impact of plastic waste on the environment. One area that strives to create beauty and environmental awareness is Cibiyuk. Through Ecobricks training, Cibiyuk residents can learn how to reduce plastic waste and create a cleaner and more beautiful environment together. This training activity was carried out together with village officials, PKK mothers, RT heads, and the entire Cibiyuk village community. The training participants were very enthusiastic about this activity. The material is presented in an interesting way. PKK mothers also participated so that the community became more enthusiastic about making ecobricks. Ecobricks themselves have a function not to destroy plastic waste, but to extend the life of these plastics by processing them into something useful, which can be used for the benefit of humans in general. Unfortunately, the manufacture of ecobricks is still not very popular among the general public so that most people still treat used plastic as household plastic waste, pollute the environment, rivers and pollute everyday life without any self-awareness